The Effect of The Mortality Rate Multiplier on Determination of Contribution to Sharia Group Life Insurance Using TMI III and TMI IV at PT Asuransi Jiwa ABC - Jihan Khafidhotin Najah; Hikmah, Yulial; Karin Amelia Safitri; Fia Fridayanti Adam (Department of Statistics, Faculty of Mathematics and Natural Sciences, Universitas Islam Bandung, 2025)
Abstract. The human mortality rate is an important factor in determining premiums. Information about mortality rates can be obtained through mortality tables that describe the probability or the probability of individual deaths. This study examines the effect of the mortality rate multiplier on gross premium determination in sharia-term life insurance using TMI III and TMI IV at PT Asuransi Jiwa ABC. This research method includes data analysis in the form of claim estimation data and claim realization data for several years from members in the Sharia group term life insurance products. The results of the analysis show that the difference in the mortality rate multiplier value between TMI III and TMI IV affects the gross premium value, especially in certain age ranges, there is a mortality rate value in TMI III that is greater than that in TMI IV, but the resulting premium value is the opposite: the premium in TMI IV is greater than the premium value in TMI III.